Nanostructures with at least one dimension in ultra-small size for the treatment of acute kidney injury. (August 2022) - Li, Yueping; Duan, Ruixue
Abstract: Acute kidney injury (AKI) has been attracting increasing attention in recent years due to its high mortality and highly associated with chronic kidney disease and end-stage kidney failure. Accumulated evidence indicates that inflammation and reactive oxygen species play important roles in the development of AKI. In fact, various drug molecules with specific antioxidant or anti-inflammatory characters have been demonstrated to be effective therapeutic drugs for AKI. Nevertheless, there are no specific medications until now because some potential drugs are limited by their low stability, poor renal targeting, and rapid clearance. Advanced nanotechnology has been devoted to providing functional nanomaterials for clinical application. Among of them, nanostructures with at least one dimension in ultra-small size have been reported that they possess renal targeting property. Taking advantages of efficiently delivering drugs to kidney or directly serving as antioxidants, such nanostructures have been regarded as promising therapeutic targets for AKI management. This review summarizes the recent advances in designing and constructing nanostructures with at least one dimension in ultra-small size to improve renal targeting and AKI management via scavenging ROS and inhibiting inflammation. Graphical abstract: Image, graphical abstract